If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8y + 2) + -1(-7y + -7) = 2 Reorder the terms: -1(2 + 8y) + -1(-7y + -7) = 2 (2 * -1 + 8y * -1) + -1(-7y + -7) = 2 (-2 + -8y) + -1(-7y + -7) = 2 Reorder the terms: -2 + -8y + -1(-7 + -7y) = 2 -2 + -8y + (-7 * -1 + -7y * -1) = 2 -2 + -8y + (7 + 7y) = 2 Reorder the terms: -2 + 7 + -8y + 7y = 2 Combine like terms: -2 + 7 = 5 5 + -8y + 7y = 2 Combine like terms: -8y + 7y = -1y 5 + -1y = 2 Solving 5 + -1y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1y = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -1y = 2 + -5 -1y = 2 + -5 Combine like terms: 2 + -5 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3
| 3(n-2)-1=2-5(n+5) | | 52=(4x+1)(x+1) | | 26+x+x+3x-34=692 | | LOG(5X-1)+LOG(X+3)=1 | | 6(4x-3)=3(8x+7) | | 6(4-3)=3(8x+7) | | 5x^4+4x^3-114x^2+36x+405=0 | | 2x(x+3)=(3x+1)(x+3) | | 7+8x-4=7x+39-3x | | (2x-7)(3x^2+7x+4)=0 | | 5r+6r=77 | | 5y^2-21y=0 | | 16r^3-9r=0 | | -2x^2+12x-13=0 | | 2x-16=x+36 | | 2t=-12 | | 0.1(0.1x+0.1)=-0.7 | | -(2w-3y-1)= | | 5.4q-1.5-4.9q=-0.5q-5.7 | | -6(3b+1)+(19b-3)=0 | | 6(3b+1)+(19b-3)=0 | | 2(a+4)=32 | | 4(x-7)=2x+8 | | r(r-5)=-6 | | 16(3x-7)=4(12x+6) | | 8+12t-3=6t+25-4t | | 2t+10t=24 | | 5(2+x)-3(3x+2)=-5 | | u=10v | | x+0.18=-0.14 | | 30+38-2x=787 | | (4W+6)-2W=(W-6)+10+14 |